Vitamin D, infections and immunity - Waldemar Misiorowski (Wiedza Medyczna, 2020)
Vitamin D (VD) is a steroid prohormone that regulates the body's calcium and phosphate levels in bone mineralization. It is also well described as a fat-soluble vitamin playing an important role in immunomodulation, regulation of cytokines, and cell proliferation. Thus, VD is a powerful hormone with pleiotropic effects, which acts to maintain optimal health. Recent studies demonstrate that VD deficiency is associated with the development of autoimmune disorders. Vitamin D generates many extraskeletal effects due to the vitamin D receptor (VDR) which is present in most tissues throughout the body. This paper reviews the recent data on the role of vitamin D in the genesis of various immunological disorders. The possible role of vitamin D in infections is implied from its impact on the innate and adaptive immune responses. A significant effect is the suppression of inflammatory processes. It inhibits immune reactions in general, but it enhances the transcription of "endogenous antibiotics" such as cathelicidin and defensins. VD inhibits the genesis of both Th1 – and Th2-cell mediated diseases. Th1 – dependent autoimmune diseases (e.g., multiple sclerosis, Type 1 diabetes, Crohn's disease, rheumatoid arthritis and so on) are also inhibited by VD due to inhibition of antigen presentation, reduced polarization of Th0 cells to Th1 cells and reduced production of cytokines from the latter cells. VD seems to also be a useful adjunct in the prevention of allograft rejection. Cardiac and coagulopathic features of COVID-19 disease deserve attention as they may be related to vitamin D. There are also intriguing potential links to vitamin D as a factor in the cytokine storm that consist some of the most serious consequences of SARS-CoV-2 infection, such as the acute respiratory distress syndrome. Finally, the current clinical data strongly associate vitamin D with SARS-CoV-2 infection, however a putative clinical link that at this time must still be considered hypothetical.